BEHAVIORAL INTENTION TO ADOPT FINTECH: STUDY OF MILLENIALS’ AND GEN-ZS’ READINESS IN INDONESIA - Zahra Ayunita Mulia; Nurhastuty Kesumo Wardhani (ZILLZELL MEDIA PRIMA, 2024)
As the financial technology (fintech) landscape develops rapidly, it is important to understand the factors that influence the adoption behavior of the Millennial and Gen-Z generation in Indonesia. This study uses a quantitative method approach to investigate the readiness of this demographic group to accept fintech solutions and identify the key determinants that shape their behavioral intentions. A structured questionnaire was administered to a representative sample of the Millennial and Gen-Z generations in Jakarta, Indonesia, to gather insights into their awareness, perceptions and attitudes towards fintech. This study draws on existing theories such as the Unified Theory of Acceptance and Use of Technology (UTAUT) to develop a theoretical framework for analyzing the factors that influence fintech adoption. This research examines variables such as performance expectations, effort expectations, social influences, and facilitating conditions to understand their impact on the behavioral intentions of Millennials’ and Gen-Zs’. The findings of this research show that the use of technology is able to contribute to achieving performance in financial transactions, apart from that the influence of the social environment is also proven to be able to increase behavior in using fintech technology. This research only tests the four core determinants of UTAUT and the data obtained is not able to represent fintech adoption behavior as a whole in Indonesia.